math

posted by .

. Prove that -x - y = -y – x; for all integers x and y.

  • math -

    -X - Y = - Y - X,
    -X + (-Y) = -Y + (-X)..
    Commutative Property: The order of addition does not matter.

    a + b = b + a.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. discrete math

    use a direct proof to show that the product of two odd numbers is odd. Proofs: (all the nos. i used are odd) 3 x 3 = 9 5 x 9 = 45 7 x 3 = 21 Yes, but you didn't prove the statement for "all" odd integers, only the odd integers you …
  2. discrete math

    Let A= {for all m that's an element of the integers | m=3k+7 for some k that's an element of positive integers}. Prove that A is countably infiite. Note: you must define a function from Z+ to A, and then prove that the function you …
  3. math

    prove -x-y=-y-x, for all integers
  4. discrete math

    Let f:ℤ+ → ℤ+ be the function defined by: for each x ∈ ℤ+, f(x) is the number of positive divisors of x. - find integers m, n, nd k so tha f(m)=3, f(n) = 4 anf f(k) = 5 -is f one-to one?
  5. math

    Let f:ℤ+ → ℤ+ be the function defined by: for each x ∈ ℤ+, f(x) is the number of positive divisors of x. - find integers m, n, nd k so tha f(m)=3, f(n) = 4 anf f(k) = 5 -is f one-to one?
  6. math help please

    Let f:ℤ+ → ℤ+ be the function defined by: for each x ∈ ℤ+, f(x) is the number of positive divisors of x. - find integers m, n, and k so tha f(m)=3, f(n) = 4 anf f(k) = 5 -is f one-to one?
  7. Math

    1) Given the arithmetic sequence an = 4 - 3(n - 1), what is the domain for n?
  8. Math, Please Help

    1) Given the arithmetic sequence an = 4 - 3(n - 1), what is the domain for n?
  9. Mathematics

    Find the coefficient of x^7 for (x-3)^11 Use the binomial theorem to expand (2y-3x)^5 Prove that (n over r)= (n over n-r) for all integers where n is greater than or equal to r and r is greater than or equal to zero Prove that (n over …
  10. Math!!! Please help!!!

    Find the coefficient of x^7 for (x-3)^11 Use the binomial theorem to expand (2y-3x)^5 Prove that (n over r)= (n over n-r) for all integers where n is greater than or equal to r and r is greater than or equal to zero Prove that (n over …

More Similar Questions